Pendidikan Akhlak pada Anak: Perspektif Al-Qur’an dan Hadist - Miftahudin, Dede Atung; Mahmudi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Throughout human history, moral issues have always been the main problem, because basically discussions about morals are always related to issues of human behavior and are the main problems for humans, especially in the context of the formation of civilization. Human behavior, directly or indirectly, is still the benchmark for knowing human actions or attitudes. The aim of this research is to find out how morals are the basis of intelligence in children and how verses and hadiths relate to moral education in children. cThe method used in this research is the research library method. The results of the research explain that humans are the most perfect creatures of the many creatures created by Allah SWT and humans are the best creatures created with intelligence, morals and intelligence. What is included in the intelligence category here is spiritual intelligence, intellectual intelligence and emotional intelligence which already exist in humans. However, these three potential intelligences will not develop if parents, family, environment and society do not stimulate children's morals. Because the basic trigger for the development of these three intelligences is morals which are formed both directly and indirectly by parents, family, environment and society. Verses and hadiths regarding moral education in children. In the surah of the Qur'an, moral education is also explained, QS Ali Imran verses 112, and 159-160. The hadith regarding moral education narrated by al-Bukhârî about mothers or families being the first madrasah for their children